In‐depth proteomics approach reveals novel biomarkers of cardiac remodelling after myocardial infarction: An exploratory analysis - Mao, Shuai (J Cell Mol Med, 2020)
Cardiac remodelling following myocardial infarction (MI) is a maladaptive change associated with progressive heart failure and compromises long‐term clinical outcome. A substantial proportion of patients afflicted by MI still develop adverse outcomes associated with cardiac remodelling. Therefore, it is crucial to identify biomarkers for the early prediction of cardiac remodelling. An in‐depth proteomics approach, including both semi‐quantitative and quantitative antibody arrays, was used to identify circulating biomarkers that may be associated with detrimental cardiac remodelling. Furthermore, statistical correlation analysis was performed between the candidate biomarkers and clinical cardiac remodelling data to demonstrate their clinical utility. A systematic proteomics approach revealed that sclerostin (SOST), growth differentiation factor‐15 (GDF‐15), urokinase‐type plasminogen activator (uPA), and midkine (MK) were increased, while monocyte chemotactic protein‐3 (MCP‐3) was uniquely decreased in MI patients who developed cardiac remodelling, compared to MI patients who did not develop cardiac remodelling and healthy humen. Moreover, correlation analyses between serum proteomes and cardiac remodelling echocardiographic parameters demonstrated a moderate positive association between left ventricular end‐diastolic volume index (LVEDVi) and the three serum proteins, uPA, MK and GDF‐15 (P < .05, respectively), and a moderate negative correlation between LV ejection fraction (LVEF) and these serum proteins (P < .05, respectively). Importantly, uPA and MK were firstly identified to be associated with the development of cardiac remodelling. The present study contributes to a better understanding of the various cytokines expressed during adverse cardiac remodelling. The identified biomarkers may facilitate early identification of patients at high risk of ischaemic heart failure pending further confirmation through larger clinical trials.